Role of the Autonomic Nervous System in Mechanism of Energy and Glucose Regulation Post Bariatric Surgery - An, Zhibo; Wang, Haiying; Mokadem, Mohamad (Frontiers in Neuroscience, 2021)
Even though lifestyle changes are the mainstay approach to address obesity, Sleeve gastrectomy (SG) and Roux-en-Y gastric bypass (RYGB) are the most effective and durable treatments facing this pandemic and its associated metabolic conditions. The traditional classifications of bariatric surgeries labeled them as “restrictive,” “malabsorptive,” or “mixed” types of procedures depending on the anatomical rearrangement of each one of them. This conventional categorization of bariatric surgeries assumed that the “restrictive” procedures induce their weight loss and metabolic effects by reducing gastric content and therefore having a smaller reservoir. Similarly, the “malabsorptive” procedures were thought to induce their main energy homeostatic effects from fecal calorie loss due to intestinal malabsorption. Observational data from human subjects and several studies from rodent models of bariatric surgery showed that neither of those concepts is completely true, at least in explaining the multiple metabolic changes and the alteration in energy balance that those two surgeries induce. Rather, neuro-hormonal mechanisms have been postulated to underly the physiologic effects of those two most performed bariatric procedures. In this review, we go over the role the autonomic nervous system plays- through its parasympathetic and sympathetic branches- in regulating weight balance and glucose homeostasis after SG and RYGB.